Is there a policy of optimal wage and income differentiation? A macroeconomic perspective - Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2000)
In this paper, we address the question of optimal wage and income dispersion in a growing economy. If already in the two-persons-case we have to deal with the fact of different marginal products of labor, there are two solutions in principle. Either two different wages are paid (at unanimous hours of working) according to these differences, or the good worker would have to work longer than the bad worker so as to equilibrate their marginal products (paying the same wage per hour). In the following parts of the paper, we limit our scope to the issue of wage/income, avoiding dealing with working hours differentiation. Furthermore, we argue on the macroeconomic level. Assuming a log-normal distribution of incomes, we determine the optimal degree of inequality and rate of per capita income growth from a model which integrates Okun's law with a social welfare function (with the Gini coefficient and the per capita growth rate as arguments) and a trade off relationship between equity and per capita growth. It is shown that modern industrial economies tend to have an "egalitarian bias" being most likely responsible for a considerable part of European unemployment. – – Gibt es eine optimale Streuung von Löhnen und Einkommen in einer wachsenden Wirtschaft? Bereits im Zwei-Personen-Fall fordern abweichende Grenzproduktivitäten der Arbeit Lösungen, wobei entweder die Löhne bei gleichen Arbeitszeiten entsprechend differenziert werden oder der bessere Arbeiter bei unverändertem Einheitslohn umso viel länger arbeitet, bis es zu einem Ausgleich der Grenzproduktivitäten kommt. Auf makroökonomischer Ebene läßt sich eine optimale Schiefe der Einkommensverteilung begründen, wenn auf (1) eine soziale Wohlfahrtsfunktion, (2) auf Okun's Law und (3) eine log-normale Verteilung der Einkommen zurückgegriffen wird. Wir unterstellen dabei (zunächst abschnittsweise) eine Trade-Off-Beziehung zwischen der Pro-Kopf-Wachstumsrate des Einkommens und der Einkommensgleichverteilung. Es zeigt sich, daß demokratische Industriegesellschaften tendenziell einen "egalitären Bias" aufweisen, der mitverantwortlich für die hohe Unterbeschäftigung in Europa sein dürfte.
Keywords: J31; O40; D63; E24; O15; 330; Income Distribution; Economic Growth; Labor Economics; Unemployment; Okun's law; Personelle Einkommensverteilung; Wirtschaftswachstum; Okun's Law; Arbeitsmarktökonomik; Lohnstruktur; Optimale Verteilung; Wirtschaftswachstum; Arbeitslosigkeit; Soziale Wohlfahrtsfunktion; Theorie; Okun's Law